2020
DOI: 10.1002/jclp.23027
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nonsuicidal self‐injury among veterans

Abstract: Objective: The current study aimed to (a) assess basic nonsuicidal self-injury (NSSI) characteristics using a validated clinical interview among a sample of veterans not recruited for specific diagnostic or environmental criteria and (b) examine the relation between NSSI and medical severity of prior suicide attempts (SAs) among veterans. Design: We conducted secondary data analyses among a combined sample of veterans (N = 165) from two parent studies conducted at a large VA Medical Center that implemented ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The lifetime prevalence of NSSI is estimated to be 6% in adults (Klonsky, 2011), although there is evidence that the prevalence of NSSI may be increasing (Klonsky, 2011; Swannell et al, 2014; Wester et al, 2018). The lifetime prevalence of NSSI appears to be slightly higher among active‐duty service members (i.e., 6.3%–7.9%; Turner et al, 2019) and even higher among military veterans, with estimates ranging from 13 to 16% (Lear et al, 2021; Monteith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime prevalence of NSSI is estimated to be 6% in adults (Klonsky, 2011), although there is evidence that the prevalence of NSSI may be increasing (Klonsky, 2011; Swannell et al, 2014; Wester et al, 2018). The lifetime prevalence of NSSI appears to be slightly higher among active‐duty service members (i.e., 6.3%–7.9%; Turner et al, 2019) and even higher among military veterans, with estimates ranging from 13 to 16% (Lear et al, 2021; Monteith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is broadly consistent with Joiner's view that NSSI is used as a mediating step in SA. Whereas in the study by Kearns et al no cases were found in which suicide attempts appeared before NSSI, the results of that study showed that the transition time from NSSI to suicide attempts was about 4.25 years in psychiatric inpatients (43) and about 7.5 years in the community population (44). We can find some differences between the two studies in terms of the time of transition and the group of subjects investigated.…”
Section: Discussionmentioning
confidence: 73%
“…Prevalence rates of lifetime NSSI are approximately 5% in the adult general population, although veterans endorse higher rates of NSSI engagement (Klonsky, 2011;Swannell et al, 2014). Rates of lifetime NSSI in non-treatment seeking veterans range from 4% to 16% with prevalence rates as high as 62% in veterans seeking treatment for posttraumatic stress disorder (PTSD; Bryan et al, 2014;Kachadourian et al, 2021;Kimbrel et al, 2015Kimbrel et al, , 2018Lear et al, 2021).…”
Section: Introductionmentioning
confidence: 99%